Incidental Ultrastructural Findings in the Sural Nerve and Dorsal Root Ganglion of Aged Control Sprague Dawley Rats in a Nonclinical Carcinogenicity Study. (January 2020) - Meier, William A.; Linn, Michael J.; Davis, Wendell P.; Sutherland, Jessica E.; Sharma, Alok K.
Xenobiotic-induced peripheral nerve damage is a growing concern. Identifying relative risks that a new drug may cause peripheral nerve injury over long periods of administration is gathering importance in the evaluation of animal models. Separating out age-related changes in peripheral nerves of rats caused by compression injury from drug-induced effects has been difficult. Biopsy of the sural nerve is utilized in humans for investigations of peripheral neuropathy, because it is largely removed from the effects of nerve compression. This study used transmission electron microscopy to identify incidental findings in the sural nerves and dorsal root ganglia of aged control rats over time. The goal was to establish a baseline understanding of the range of possible changes that could be noted in controls compared to rats treated with any new investigative drug. In this evaluation, most sural nerve fibers from aged control rats had few ultrastructural abnormalities of pathologic significance. However, glycogenosomes, polyglucosan bodies, swollen mitochondria, autolysosomes, split myelin, Schwann cell processes, and endoneural macrophages with phagocytosed debris (considered an indication of ongoing degenerative changes) were occasionally noted.